ASSESSMENT OF THE QUALITY OF LIFE OF PATIENTS AFTER RESTRICTIVE BARIATRIC SURGERY - Savoliuk, S.I.; Zavertylenko, D.S.; Kruhliak, Y.K. (World of Medicine and Biology, 2022)
According to a number of scientific articles, after performing restrictive metabolic operations, in some patients, the severity or development of de novo symptoms of gastroesophageal reflux disease is determined, which affects the quality of life of patients. The relevant problem creates the urgency to investigate the quality of life of patients after restrictive operations and search for preventive measures to prevent this complication. In the relevant study, the presented data were obtained in the period from 2016 to 2019 during 1 year of postoperative follow-up of 49 bariatric patients, who were divided into 3 comparison groups, depending on the type of restrictive surgery (sleeve gastrectomy, greater curvature plication or fundogastroplication (greater curvature plication combine with Nissen fundoplication). One year after surgery, all 3 groups had positive weight reduction results, and compensation of accompanying pathology were noted. Also, an increase in the general quality of life indicator was noted, according to the results of the questionnaire, with a slight advantage of the indicators obtained in the III group of patients, which is associated with the absence of manifestations of gastroesophageal reflux disease and reflux esophagitis after 1 year. According to the obtained results, simultaneous surgery in the form of a combination of Nissen gastroplication and fundoplication in the treatment of patients with obesity and metabolic syndrome allows for achieving positive results of weight reduction and compensation of comorbid diseases, which is comparable and relative to classical surgical techniques and makes it possible to prevent the development of postoperative complications, which improves the quality of life of patients.
Keywords: laparoscopy; simultaneous surgery; bariatrics; gastroesophageal reflux; reflux esophagitis; metabolic syndrome; quality of life